2018
DOI: 10.1101/431528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bridging the spatiotemporal scales of macromolecular transport in crowded biomimetic systems

Abstract: Crowding plays a key role in the transport and conformations of biological macromolecules. Gene therapy, viral infection and transfection require DNA to traverse the crowded cytoplasm, including a heterogeneous cytoskeleton of filamentous proteins. Given the complexity of cellular crowding, the dynamics of biological molecules can be highly dependent on the spatiotemporal scale probed. We present a powerful platform that spans molecular and cellular scales by coupling single-molecule conformational tracking (S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 56 publications
(105 reference statements)
1
21
0
Order By: Relevance
“…Further, this increased transport is coupled with larger conformations, at odds with the Newtonian Stokes relationship (D ~ Rcoil-1). We previously showed that linear DNA diffusing in a network of semiflexible actin filaments was more compact and displayed more extreme subdiffusion and lower transport coefficients than when diffusing in a network of more rigid microtubules (19). Further, recent simulations have shown that the slow mobility of large crowders, which results in continuous temporal evolution of the crowding mesh, was required for true anomalous subdiffusion (67).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, this increased transport is coupled with larger conformations, at odds with the Newtonian Stokes relationship (D ~ Rcoil-1). We previously showed that linear DNA diffusing in a network of semiflexible actin filaments was more compact and displayed more extreme subdiffusion and lower transport coefficients than when diffusing in a network of more rigid microtubules (19). Further, recent simulations have shown that the slow mobility of large crowders, which results in continuous temporal evolution of the crowding mesh, was required for true anomalous subdiffusion (67).…”
Section: Discussionmentioning
confidence: 99%
“…These analysis methods, depicted in Figure 1, have been described and validated previously (19)(20)(21)35). (19,(62)(63)(64). Each ROI is analyzed individually and averaged together post-analysis (Fig.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Few studies have investigated composite networks of actin and microtubules 11,27,57,58 due, in part, to the incompatibility of standard polymerization conditions for each protein 27 . However, methods have recently been introduced to co-polymerize actin and tubulin in situ to create randomly-oriented co-entangled composites of actin and microtubules 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Differential Dynamic Microscopy. Following our previously described methods, 57,58 where ( ) is the nonergodicity parameter, ( ) is the decay time, and ( ) is the stretching exponent. Using methods similar to those described by Cho et al 38 , we obtain both ( ) and ( ) prior to curve fitting.…”
Section: Discussionmentioning
confidence: 99%